Optical properties of SrxBa1−xNb2O6 nanoscale films (x = 0.5 and 0.61) grown by RF-cathode sputtering in an oxygen atmosphere - S. V. Kara-Murza (World Scientific Publishing, 2021)
The research findings of the phase composition, nanostructure and optical properties of strontium–barium niobate thin films are discussed. SrxBa1−xNb2O6 nanosized films (x = 0.5 and 0.61) were characterized by XRD, SEM and AFM studies. Reflective multi-angle ellipsometry and spectrophotometry were used to determine the optical parameters (refractive index, its dispersion, and thickness of the damaged surface layer) of thin films. It was shown that SBN-50 and SBN-61 thin films were grown c-oriented on Al2O3 (0001) and heteroepitaxial on MgO (001) substrates. The increase of refractive index, approaching its maximum value in the bulk material for a given composition as the film thickness increases, is observed.